A Germline Variant at 8q24 Contributes to the Serum p2PSA Level in a Chinese Prostate Biopsy Cohort - Lin, Xiaoling; Wu, Yishuo; Liu, Fang; Na, Rong; Huang, Da; Xu, Danfeng; Gong, Jian; Zhu, Yao; Dai, Bo; Ye, Dingwei; Yu, Hongjie; Jiang, Haowen; et al. (Frontiers in Oncology, 2021)
Introduction: The clinical performance of [-2]proPSA (p2PSA) and its derivatives in predicting the presence and aggressiveness of prostate cancer (PCa) has been well evaluated in prostate biopsy patients. However, no study has been performed to evaluate the common genetic determinants which affect serum p2PSA level. Materials and Methods: Here we performed a two-stage genome-wide association study（GWAS） of p2PSA level in Chinese men who underwent a trans-perineal ultrasound guided prostate biopsy at Huashan Hospital, Shanghai Cancer Center and Ruijin hospital in Shanghai, China. Germline variants significantly associated with p2PSA level in the first stage (N = 886) were replicated in the second stage (N = 1,128). Multivariate linear regression was used to assess the independent contribution of confirmed SNPs and known covariates, such as age, to the level of p2PSA. Results: A novel nonsynonymous SNP rs72725879 in region 8q24.21 at PRNCR1 gene were significantly associated with serum level of p2PSA in this two-stage GWAS (P = 2.28 ×10-9). Participants with homozygous ‘T’ alleles at rs72725879 had higher p2PSA levels compared to those allele ‘C’ carriers. This variant was also nominally associated with PCa risk (P-combined = 3.44 ×10-18). The association with serum p2PSA level was still significant after adjusting for PCa risk and age (P = 0.017). Conclusions: Our study shows that the genetic variants in the 8q24.21 region are associated with serum level of p2PSA in a large-scale Chinese population. By taking inherited variation between individuals into account, findings of these genetic variants may help improve the performance of p2PSA in predicting prostate cancer.